Correlation Between Thioredoxin-Interacting Protein and Nerve Conduction Velocity in Patients With Type 2 Diabetes Mellitus - Gao, Yuan; Chen, Shuchun; Peng, Minmin; Wang, Zi; Ren, Luping; Mu, Shumin; Zheng, Meiling (Frontiers in Neurology, 2020)
Aims: To investigate the correlation between thioredoxin-interacting protein (TXNIP) and peripheral nerve conduction velocity (NCV) in patients with type 2 diabetes mellitus. Methods: In total, 338 patients with type 2 diabetes mellitus (T2DM) were included in this study. We collected the clinical data and measured the velocity of bilateral ulnar nerve movement, ulnar nerve sensation, median nerve movement, median nerve sensation, common peroneal nerve movement and superficial peroneal nerve sensory conduction. According to the results, the patients were divided into two groups: normal peripheral nerve conduction group (NCVN group) and abnormal peripheral nerve conduction group (NCVA group). The two groups were then compared in terms of the conventional biochemical index and the sugar metabolic index as well as the serum levels of TXNIP, reduced glutathione (GSH), total superoxide dismutase (SOD), malondialdehyde (MDA), and tumor necrosis factor alpha (TNF-α). The correlation between TXNIP and NCV was also analyzed. Results: Compared with the NCVN group, the TXNIP and MDA values were significantly increased in the NCVA group (P < 0.05). Among the patients with T2DM, age, fasting glucose, SDBG and TXNIP were risk factors for NCV abnormality, while vitamin D3 was a protective factor. After adjusting for related confounding factors, TXNIP was significantly correlated with NCV (P < 0.05). Among the patients with T2DM, TXNIP was an independent risk factor for left ulnar motor conduction velocity (MCV), right ulnar MCV, left median MCV, and right median MCV. TNF-α was identified as a positive influencing factor for serum TXNIP, while serum TXNIP was a positive factor for TNF-α and MDA (both P < 0.05). Conclusion: Serum TXNIP is related to NCV in T2DM patients. In combination with oxidative stress and inflammation, TXNIP may affect diabetic peripheral neuropathy (DPN).